Heat dissipation characteristics of anode saturable reactors with high thermal conductivity epoxy resin used for ultra‐high‐voltage direct current converter valves. Issue 5 (1st October 2020) - Wei, Yang; WeiJiang, Chen; Yuan, Zhou; Chong, Zhang; Zhuo, Zhang; Xin, Chen; YuShun, Zhao; XingMing, Bian
Abstract : A saturable reactor is one of the important components of converter valves in high‐voltage direct current transmission systems. With the ever‐increasing capacities of converter valves, the heat losses generated by saturable reactors are also increasing. Thus, a thermal–fluid mechanics coupled heat dissipation model for saturable reactors is proposed. In order to study the factors affecting the thermal dissipation in the saturable reactor, the epoxy resin insulating layers with different thermal conductivity were considered in this work. The simulation results showed that the hot spots in the saturable reactor are on the iron core and close to the pipe inlet that most of the generated heat can be extracted by a cooling pipe and that the effect of heat dissipation can be improved by raising the thermal conductivity of the epoxy resin. The thermal conductivities of the epoxy resin used in the two reactors were 0.8 and 1.2 W/mK, respectively. The time dependence of the iron core temperature was in accordance with the simulation results and the maximum temperatures of the saturable reactor were also consistent with the simulation results. By increasing the thermal conductivity of the epoxy insulation layer, the temperature of the iron core could be significantly reduced.